Studi Optimasi Pengaruh Tekanan dan Waktu Pengeringan terhadap Kadar Air Ikan pada Proses Freeze Drying - Dzaky Mirza Pradana; Widjanarko Widjanarko (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to evaluate and optimize the effects of vacuum pressure and drying time on moisture content in the freeze drying process. Freeze drying was selected due to its ability to preserve the quality of food products by removing moisture through sublimation under low vacuum conditions. The vacuum pressure variables applied in this study were -62.8 cmHg, -64 cmHg, -67 cmHg, -70 cmHg, and -71.2 cmHg, while the drying times were varied at 8.2 hours, 9 hours, 11 hours, 13 hours, and 13.8 hours. Response Surface Methodology (RSM) with a Central Composite Design (CCD) was employed to analyze the individual effects and interactions of the two factors on final product moisture content. The results showed that both vacuum pressure and drying time significantly influenced moisture reduction, while their interaction effect was statistically insignificant. The optimum conditions were achieved at a vacuum pressure of -70.5 cmHg and a drying time of 12.6 hours, meeting the moisture content requirements based on SNI 8273:2023 standards. These findings are expected to serve as a practical reference for determining optimal operating parameters in freeze drying processes to improve efficiency and product quality.